Social Work Technology: Utilization of E-Counseling for Assessment Services - Willya Achmad (Jurnal Info Sains : Informatika dan Sains, 2023)
This study aims to explore the use of technology in the field of social work through the implementation of e-counseling services in the context of assessment. The development of information and communication technology has provided new opportunities for providing counseling services online, which can expand the reach of social work services to people in need. This study adopts a qualitative approach using a descriptive study method. The results of this study reveal the positive potential of using e-counseling in social work assessment services. The main benefits include increased service accessibility, time flexibility, privacy for service participants, and automatic data processing. However, the research also identified several challenges, such as expanding technological capabilities for social workers, deep understanding of E-Counseling ethics, technical challenges in ensuring data security and confidentiality and effectiveness in providing assessments because they are not face to face. This research contributes to broadening insights about the use of technology in the field of social work, especially in assessment services. The practical implication of this research is the expansion of social work assessment services through the E-Counseling platform, taking into account the ethical, data security and training aspects of social workers.